2013
DOI: 10.4103/0972-124x.107479
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the effectiveness of subpedicle acellular dermal matrix allograft with subepithelial connective tissue graft in the treatment of isolated marginal tissue recession: A clinical study

Abstract: Introduction:The most common problem encountered in our day to day practice is exposed root surface or a tooth getting long. The main indication for root coverage procedures are esthetics and/or cosmetic demands followed by the management of root hypersensitivity, root caries or when it hampers proper plaque removal. Over the years, various techniques have been used to achieve root coverage.Aim and Objectives:The aim of this study was to compare the effectiveness of subpedicle acellular dermal matrix allograft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 8 publications
3
18
0
Order By: Relevance
“…These findings are in accordance with previous studies by Shori et al and Guan et al [7,12]. SCTG has been known to provide the best rootcoverage outcomes; its predictability is as high as 95% for Miller's Class I and II cases [13,14].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are in accordance with previous studies by Shori et al and Guan et al [7,12]. SCTG has been known to provide the best rootcoverage outcomes; its predictability is as high as 95% for Miller's Class I and II cases [13,14].…”
Section: Discussionsupporting
confidence: 83%
“…This technique offers higher levels of root coverage than other techniques due to the dual blood supply is given to the graft; better esthetics and good postoperative healing at the donor site are other benefits [5,6]. SCTG has also been found to increase the width of keratinized gingiva significantly [7]. However, the graft needs to be harvested from the palate, meaning that the technique demands an intricate second surgical procedure, which adds to patient morbidity levels and surgical chair time [3].…”
Section: Introductionmentioning
confidence: 99%
“…Forty‐eight studies (reported in 57 papers) were included in the review, with 20 providing data for meta‐analyses. Nine RCTs had their data reported in two articles each (i.e., according to the follow‐up period or type of data (i.e., clinical or patient‐reported outcomes) .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 101 articles 30‐131 with 94 RCTs potentially eligible for inclusion into the pooled estimates were identified in the base of evidence, and their main characteristics (i.e., number and age of participants, interventions, follow‐up period, number of sites exhibiting CRC, MRC [percentage], use of RMAs, randomization, allocation concealment, masking of examiners, completeness of the follow‐up period, and risk of bias) are depicted in Table 2 30‐131 . Seven studies were reported in two articles each, and their data were reported under one study name 37,38,57,58,65,66,83,84,90,91,110,111,115,116 …”
Section: Summary Of What Other Srs Have Evaluatedmentioning
confidence: 99%
“…Of the 94 trials included in Table 2, 52 were included in the following sets of meta‐analyses: 1) ADMG/CM + CAF versus SCTG‐based procedures; 31,66,76,97,102,114 2) ADMG/CM + CAF versus CAF; 57,58,86,125 3) BS + GTR with resorbable membranes (RS) + CAF versus GTR with RS + CAF; 62,63,78,101 4) EMD + CAF versus CAF; 51,53,59,71,94,103,115,116 5) EMD + CAF versus SCTG + CAF; 30,32,90,91 6) GTR with RS + CAF versus CAF; 36,83,84 7) GTR (all types of membrane) + CAF versus SCTG‐based procedures; 35,43,55,74,96,101,107,109,117,122,123,126 8) SCTG‐based procedures versus CAF; 40,41,54,56,80 9) SCTG + CAF versus SCTG (epithelial collar); 44,47 10) SCTG‐based procedures, micro versus macro procedures; 42,46 and 11) SCTG‐based procedures versus FGG 70,100 . All of the comparisons were performed using studies reporting data on single defects, except for one comparison on EMD + CAF versus CAF 53,71 that could also be conducted using data on multiple recessions.…”
Section: Summary Of What Other Srs Have Evaluatedmentioning
confidence: 99%